Al-Ummah fī Indūnīsīya: Mafhūmuhā, Wāqi‘uhā wa Tajrībatuhā - Shihab, M. Quraish (Studia Islamika, 1994)
Islam has undergone several renewals throughout its long history in Indonesia. These renewals have resulted in stratifications leading to the formation of sects within Indonesian Muslim community. Meanwhile, Hinduism and Buddhism -  the two dominant religions which came before Islam - still exist amongst a small number of the population, and Christianity is gaining more adherents. In effect Indonesia is becoming an ethnically, religiously and professionally pluralistic nation. Differences in opinion are thus unavoidable.DOI: 10.15408/sdi.v1i1.867